RISK AND PROTECTIVE FACTORS TO PREVENT RECIDIVISM OF MINORS IN CRIMINALITY, A PREVENTIVE APPROACH IN CRIMINAL JUSTICE - Sota, Marinela; Agolli, Irida (European Scientific Journal, ESJ, 2015)
The model of risk and protective factors results as a model that is in full agreement with the principles of literature “What works” in the field of criminal sentences. Ministry of Justice in Albania has not developed yet a model to address recidivism, especially recidivism of minors and young age. Despite the fact that Probation Service and General Directorate of Prisons, lately in the main documents of assessing offenders have reflected the preventive approach, there is no an integrated strategy to address recidivism according to the model of risk and protective factors. The discussion presents the principles of preventive approach in the field of criminal sentences and in this frame the model of risk and protective factors it’s viewed as an approach to be accepted from the policymakers as the only effective strategy addressing recidivism.